Novel 60 GHz Band Spatial Synthetic Exposure Setup to Investigate Biological Effects of 5G and Beyond Wireless Systems on Human Body - Hikage, Takashi; Ozaki, Ryunosuke; Ishitake, Tatsuya; Masuda, Hiroshi (Frontiers in Public Health, 2021)
The global spread of 5th generation (5G) wireless systems causes some concern about health effects of millimeter waves (MMW). To investigate biological effects of local exposure to 5G-MMW on human body, a novel 60 GHz band exposure setup was developed, and its performance was validated. A spatial synthetic beam-type exposure setup using two dielectric lens antennas was proposed to achieve high intensity 60 GHz irradiation to the target area of human skin. Variety distributions and intensities of electromagnetic fields at the exposed area, which is modified by incident angles of the combined beams, were simulated using finite-difference time-domain methods. The exposure performance we estimated was verified by temperature elevations of surface in a physical arm-shaped silicone phantom during the MMW exposure. The interference fringes generated in the exposed area due to the combined two-directional beam radiations were observed both in the simulation and in the phantom experiment but eliminated by applying an orthogonalizing polarized feeding structure. Under these exposure conditions, the local temperature changes, which could evoke warmth sensations, were obtained at the target area of the human forearm skin, which means the achievement of exposure performance we intended.